The effects of differential and variable training on the quality parameters of a handball throw - Wagner, H.; Müller, E. (Sports Biomechanics, 2008)
The aim of this study was to undertake a comprehensive temporal, effective, and practical training study (variable and differential learning) that would offer athletes the opportunity to increase their performance, and to analyse the effects by measuring kinematics and quality parameters. Two participants of differing standards - a player of the first Austrian League and an Olympic and World Champion - but of similar anthropometric characteristics were recruited. One of the participants (Austrian League) was tested on five different occasions (pre-test and four retests) to measure the effects of four different training phases using kinematic analysis. The results of the study indicate an increase in ball velocity within the differential training phases (first, second, and fourth phases), different proximal-to-distal sequences of the participants, and a change of movement pattern during training measured by the segment velocities and the angle-time courses.